2010
DOI: 10.1093/jac/dkq015
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of oseltamivir: an oral antiviral for the treatment and prophylaxis of influenza in diverse populations

Abstract: Influenza is a transmissible viral pathogen that continues to cause substantial morbidity and mortality. Oseltamivir is an orally administered antiviral medication that selectively inhibits the influenza neuraminidase enzymes that are essential for viral replication. Treatment of infected children ≥1 year and adults of all ages may decrease the severity and duration of the symptoms of infection, while prophylactic dosing can prevent their onset. Oseltamivir is ingested in the form of a prodrug (oseltamivir pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
156
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(164 citation statements)
references
References 24 publications
8
156
0
Order By: Relevance
“…Ariano and colleagues recently demonstrated that the pharmacokinetics of oseltamivir carboxylate are not reduced in critically ill patients across a weight range of approximately 50 to 200 kg (2). The median (interquartile range [IQR]) AUC 0-ϱ in critically ill patients with normal kidney function was 4,854 (3,109, 10,820) ng ⅐ h/ml (2), compared to a median (IQR) AUC 0-ϱ of 4022 (3,481,4,747) ng ⅐ h/ml in the current study (noncompartmental estimate). Similar to our findings, Ariano and colleagues also demonstrated that pharmacokinetic parameters of oseltamivir carboxylate are not influenced by body weight (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ariano and colleagues recently demonstrated that the pharmacokinetics of oseltamivir carboxylate are not reduced in critically ill patients across a weight range of approximately 50 to 200 kg (2). The median (interquartile range [IQR]) AUC 0-ϱ in critically ill patients with normal kidney function was 4,854 (3,109, 10,820) ng ⅐ h/ml (2), compared to a median (IQR) AUC 0-ϱ of 4022 (3,481,4,747) ng ⅐ h/ml in the current study (noncompartmental estimate). Similar to our findings, Ariano and colleagues also demonstrated that pharmacokinetic parameters of oseltamivir carboxylate are not influenced by body weight (2).…”
Section: Discussionmentioning
confidence: 99%
“…Oseltamivir carboxylate is a small molecule (284.4 g/mol) that is virtually unbound to plasma proteins (3% protein binding) (4). Thus, lung exposures may be inferred from oseltamivir carboxylate plasma concentration-time data.…”
Section: Discussionmentioning
confidence: 99%
“…Oseltamivir phosphate (Tamiflu), an ethyl ester prodrug of the active metabolite Ro 64-0802 (oseltamivir carboxylate), is used for the treatment and prophylaxis of influenza A or B in adults and children Ն1 year of age (Moscona, 2005;Davies 2010). The prodrug is well absorbed (75-80%) from the gastrointestinal tract and is efficiently converted by human liver carboxylesterase 1 to Ro 64-0802 (Shi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Oseltamivir phosphate (OP) was recommended by the World Health Organization (WHO) for both treatment and prophylaxis of influenza. As an important firstline defense in the event of a flu pandemic, it has been licensed to Hoffmann-La Roche Ltd. under the trade name Tamiflu Õ (Davies, 2010). As a pro-drug, OP can be readily absorbed from the gastrointestinal tract whose absolute bioavailability is about 75-80% and extensively converted by hepatic carboxylesterases to the active metabolite oseltamivir carboxylate (OSCA), a potent and selective inhibitor of influenza virus neuraminidase (Heinig & Bucheli, 2008;Dutkowski et al, 2010) that is essential for the release of progeny influenza viruses from infected host cells, which in turn prevents infection of new host cells and viral spread throughout the respiratory tract (Ghosh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%